Healthy Living Culture Counseling - M. Ilyas; Een Endasari; Mawaddah; Tri Mulia Franchika (Asian Journal of Healthcare Analytics, 2022)
Many people do not really understand how to live a healthy life, this can be seen from the way of life of people who still do not keep their environment clean, so there needs to be an activity to transfer knowledge to the community in order to live a healthy life. To increase knowledge about the importance of healthy living, counseling participants were given basic knowledge materials about: Behavior in relation to clean water, behavior in relation to sewage disposal, behavior in relation to waste, both solid and liquid waste, behavior in relation to a house that behaves in a clean and hygienic manner. healthy (ventilation, lighting, humidity, floors and so on), behavior related to cleaning mosquito nests. The method used is the lecture and question and answer method. Based on the results of the activities carried out, it turned out that in general there was a fairly good response, namely the enthusiasm of the counseling participants to ask further questions. It is also hoped that from this activity participants can also pass on the knowledge that has been obtained to other communities.